ANALISIS KINERJA KEUANGAN PEMERINTAH PROVINSI SUMATERA SELATAN - VANADHIA RAHMATIKA WELLYAN; EVA NOVARIA; LISDIANA LISDIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research analyzes financial performance and management in South Sumatra Province, with a focus on financial ratio analysis and the impact of autonomy. Primary and secondary data were used, involving in-depth interviews and document analysis. Regional financial performance is evaluated with the efficiency ratio, measuring the cost of revenue. There were fluctuations in performance during 2019-2021, with efficient provincial finances in 2019 and 2020, but a decline in 2021. The financial independence ratio measures dependence on local revenue. South Sumatra Province has